Performance Evaluation with Large-Scale Solar PV Integration to Grid: A Case Study of Nepalese Transmission Networks - Adhikari, Anjan; Neupane, Sandeep; Chaulagain, Nabin Raj; Chaudhary, Jeetendra (Journal of Science and Engineering, 2025)
To mitigate carbon footprints and meet growing energy demands, Nepal is increasingly focusing on the development of clean and renewable energy sources. Currently, the nation primarily relies on hydropower for electricity generation, supplemented by a few solar photovoltaic (PV) projects. As outlined in the Energy Development Roadmap 2081, Nepal aims to install a total electric capacity of 28,500 MW and export 15,000 MW to neighboring countries by 2035. To achieve these goals, the government is planning to integrate solar PV power plants into the national grid alongside hydropower. In alignment with this strategy, the Nepal Electricity Authority (NEA) has recently issued Letters of Intent (LOI) for grid connections of solar power plants in various regions. This study investigates the impact of integrating Photovoltaic power plants into the existing 33 kV and 132 kV transmission networks in the Parasi and Nawalpur districts, located in the mid-southern region of Nepal. Utilizing the ETAP platform, comprehensive analyses, including load flow, flicker, short circuit, and transient frequency studies, were conducted to evaluate the effects of PV penetration at multiple grid locations. The findings offer valuable insights into the impacts on grid performance and present concrete recommendations to ensure grid stability and reliability during the transition to a more renewable energy mix.